A rapid liquid chromatography-tandem mass spectrometry based method for the detection of Tet(X) resistance gene in Enterobacteriaceae - Zhang, Liyun; Xie, Jie; Qu, Ziyu; Duan, Duan; Liu, Chujun; Zhang, Di; Jiang, Haiyang; Dai, Xinhua; Jiang, You; Fang, Xiang; Wu, Congming (Frontiers in Microbiology, 2024)
There is a major public health threat posed by antibiotic resistance around the world. Tigecycline overcomes the resistance mechanisms of traditional tetracyclines and is often seen as the final resort in combating infections caused by bacteria resistant to multiple drugs. However, the introduction of new mobile tet(X) tetracycline destructases is leading to a notable rise in tigecycline resistance. Therefore, a rapid detection method is needed to monitor the spread of tigecycline resistance. In this study, a novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) method to detect tet(X) in bacterial isolates was developed. This method utilized the analysis by LC-MS/MS of metabolite ratios to determine the presence of tet(X). Bacterial suspensions were co-incubated with tigecycline for 1 h, where tet(X) destructase inactivated tigecycline, making a particular metabolite with a 16-Da change in mass. The characterized quantitative ion pairing of tigecycline in the ESI positive mode was observed at 586.1 → 569.1 m/z. The oxygenated tigecycline detection was established at 602.2 → 529.1 m/z. A model was established using 35 tet(X)-positive and 15 tet(X)-negative Enterobacteriaceae strains in this study to optimize the cutoff value. Applying the model to analyze 70 bacterial isolates, the sensitivity of the LC-MS/MS test was 98.9% compared to polymerase chain reaction (PCR), and specificity was 100%. This method is rapid and easy to operate, providing results within 1 h, making it more suitable for routine use in clinical microbiology laboratories.